Business Risk, Firm Size, and Debt Policy on Firm Value: The Mediating Role of Financial Performance - Sosnon Putri Halawa; Sukrisno Sukrisno (UNIVED Press, 2026)
This study aims to examine the effect of Business Risk (RISK), Firm Size (SIZE), and Debt Policy (DER) on Firm Value (PBV) with Financial Performance (ROA) as a mediating variable in non-financial companies listed on the Indonesia Stock Exchange. The study population includes all companies in the non-financial sector listed on the Indonesia Stock Exchange, and the sample selection was carried out using purposive sampling with criteria of financial reporting consistency, full availability of variable data, and continuous recording during the observation period 2020-2024. This study uses secondary data in the form of annual financial statements obtained from the official website of the Indonesia Stock Exchange and is analyzed using path analysis with the Baron and Kenny procedure through SPSS version 26 software. The results show that RISK has a negative and significant effect on ROA, SIZE has a positive and significant effect on ROA as the most dominant determinant, and DER has a negative and significant effect on ROA. ROA has a positive and significant effect on PBV. Mediation testing proves that ROA significantly mediates the effect of all three independent variables on PBV through partial mediation. This study provides theoretical implications in strengthening the trade-off theory and signaling theory, managerial implications regarding the importance of optimally managing asset scale and leverage, and regulatory implications regarding the need for increased transparency in the disclosure of financial risks by public non-financial companies in the Indonesian capital market.